Inclusive Approach for Strengthening of Agri-business Start-ups Ecosystem - Bharimalla, A K; Mahawar, Manoj Kumar; Patil, P G (Indian Farming, 2020)
ICAR-Central Institute for Research on Cotton Technology (CIRCOT) has served the cotton community since its inception in 1924 and has evolved over the years to address the changing needs of its stakeholders. The institute is committed to carry basic and strategic research on processing of cotton and its agro-residues leading to development of value added products as well as quality assessment of fibre. It is the first textile institute in India to become a Referral Laboratory for Cotton Textiles. Calibration cotton, a standard reference material is hallmark of the institute’s R&D with 300 corporate users. It is preferred over USDA Calibration Cotton which is an import substitute. Further, institute is working on value addition to cotton biomass through particle board preparation, compost making, nanocellulose production, cottonseed oil etc. to provide additional income to cotton growers.